Intermittent diplopia and ptosis as presenting signs of seropositive ocular myasthenia gravis following COVID-19 infection - Keith, Thomas; Mills, Megan (Canadian Journal of Optometry, 2023)
A 65-year-old man presented to the eye clinic with non-specific blurry vision, mild intermittent horizontal diplopia, subtle intermittent left upper eyelid ptosis, and poor balance following an untreated COVID-19 infection three weeks prior. Ocular findings were variable and inconsistent over the course of two examinations. Intermittent ptosis and diplopia, followed by the development of shortness of breath, led to acetylcholine receptor antibody testing, which provided a positive result. The patient was diagnosed with post-infectious seropositive myasthenia gravis and successfully treated with pyridostigmine and prednisone. In this case report, healthcare providers are alerted to the possibility of new-onset myasthenia gravis following recent COVID-19 infection.